How just is Just: financing transition towards SDG_7 in the Eastern Cape, South Africa - Dlulane, Jean (Graduate School of Business (GSB), 2025)
It is widely confirmed that the average annual global greenhouse gas emissions are at their highest and there is an immediate need to limit global warming to 1.5 °C. South Africa is ranked among the biggest sources of greenhouse gases as its economy is dominated by the use of fossil fuel with 80% of its power being generated from coal. The government made commitments to reduce its domestic carbon emission by 2030 whilst ensuring just pathways of transitioning to cleaner sources of energy. The United Nations's 2030 SDG7 seeks to ensure universal access to affordable, reliable, and modern sources energy and which is closely linked to the foundations of the National Development Plan adopted as South Africa`s development roadmap. At the heart of the Just Energy Transition (JET) framework lies the principles of equity, fairness, and accessibility to clean energy resources and the finance needed to transition to renewable sources of energy to strategically reduce the negative effects of climate change. It is against this background that this research sought to understand the socio-culturally shaped community attitudes and perceptions towards the JET framework and its long-term sustainable benefits. This research also explored the challenges faced by municipalities in funding initiatives for renewable energy and universal energy access in the Eastern Cape. Data was collected using semi-structured, open- and closed-ended questions and face-to-face interviews using both isiXhosa and English with 10 village residents and five municipal representatives across various municipalities in the Eastern Cape. Using an interpretivism epistemology approach, the qualitative thematic analysis revealed that while climate change has negatively impacted livelihoods, communities did not know nor understand the JET framework principles or how to harness their indigenous knowledge as just pathways to strategically reduce the effects of climate change. There seemed to be a disconnect between community experiences and government initiatives, highlighting the need for enhanced community education and improved local government involvement in sustainable development dialogues, and clearer communication of government policies. Thematic analysis also revealed the financial challenges faced by the municipalities, varying from poor revenue collection, escalating debt, and high unemployment rates as well the lack of access to funding due to their poor financial performance and qualified audit reports. Lack of political will among local municipality representatives to embrace renewable energy initiatives was noted, and as a result municipalities failed to promote grassroots sustainable development, further exacerbating agency issues with electricity distribution and service delivery. The research recommends community-driven grants funding to facilitate dialogues and education on renewable energy benefits and legal frameworks that ensure communities have a meaningful voice in decision-making processes integrating indigenous knowledge with modern sustainable technologies. National government policies need to align with local realities and needs, funding models need to be reformed to support community-driven renewable energy projects even for non-bankable projects.